Embryo splitting can increase the quantity but not the quality of blastocysts - Hsun-Han Tang; Yung-Chieh Tsai; Cheng-Tsung Kuo (Elsevier, 2012)
Objective: In this study, we investigated the developmental potential of single blastomeres that were obtained from 4-cell mice embryos that were split during the blastocyst stage. Materials and Methods: Imprinting Control Region (ICR) mice (age: 6-8 weeks), were superovulated and mated with a single fertile male of the same strain. We obtained 2-cell embryos that were then cultured in 4 groups (×4) with Human tubal fluid (HTF) supplemented with 12% fetal bovine serum. When these embryos reached the 4-cell stage, their zonae pellucidae were removed and every single blastomere was isolated by repeated pipetting with Ca/Mg2+-free medium. The isolated blastomeres (study group) and the intact embryos (control group) were then cultured to determine the blastocyst formation rate and quality. Results: We collected a total of 936 embryos from 524 morphologically intact, top-grade embryos in the 4-cell stage from 80 stimulated mice. We used 356 of these embryos to isolate the blastomeres. The remaining 168 embryos were cultured as controls. A total of 1312 single blastomeres were obtained and cultured in vitro. Among these, 620 blastocysts were harvested from the original embryos compared with 136 blastocysts that were harvested from the control group. The overall blastocyst formation rate was 174.2% (620 blastocysts from 356 embryos) for the study group compared with 81.5% (136 blastocysts from 168 embryos) for the control group. The study group was 43.3% (268 of 620) top-grade blastocysts compared with 91% (152 of 168) of the control group. Taken together, the percentage of top-grade blastocysts obtained per original embryo in the split group was 75.4% (174.2%×43.3%) compared with 74.2% (81.5%×91%) for the control group. Conclusions: Embryo splitting can increase the number of blastocysts. However, the percentage of available top-grade blastocysts is the same compared with nonsplit embryos. Embryo splitting may not be a cost-effective technique for the generation of high-quality mouse blastocysts.